HIV in pregnancy – An update - Victor N. Chilaka (16936929) (2020)
Human immunodeficiency virus (HIV) is an infection with a global prevalence and currently no cure or vaccine. Women living with HIV who become pregnant or who acquire the virus during pregnancy are at risk of both maternal and perinatal morbidity and mortality mainly if the virus is poorly controlled. Furthermore, there is a risk of vertical transmission to the fetus during pregnancy labour and postpartum through breastfeeding. Appropriate management must be instituted to reduce the consequences of HIV in pregnancy, ideally starting with preconception counselling and planning pregnancies when the viral load is minimum. During pregnancy, an appropriate combined anti-retroviral (cART) medication is mandatory with very close monitoring of the viral load, cluster of differentiation 4 (CD4) cell counts, blood counts, liver and kidney function tests. Planning delivery should not be different in women on cART and suppressed viral loads. However, special care must be taken to limit vertical transmission in those who present late and in whom viral load is unknown or not controlled at the time of delivery. Breastfeeding remains a potential source of infection for the baby and is being discouraged in highincome countries for women living with HIV; however, in low-income countries, the recommendation is exclusive breastfeeding. If breastfeeding must happen, it is best when viral load is suppressed, and cART continued until weaning. Serodiscordant couples present unique problems, and their management should begin with the planning of pregnancy. Emphasis should be on taking steps to prevent HIV transmission to the negative partner and vertical transmission to the new-born. Other Information Published in: European Journal of Obstetrics & Gynecology and Reproductive Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejogrb.2020.11.034